2020
DOI: 10.1038/s41386-020-0765-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex and strain differences in dynamic and static properties of the mesolimbic dopamine system

Abstract: Sex is a biological variable that contributes to the incidence, clinical course, and treatment outcome of brain disorders. Chief among these are disorders associated with the dopamine system. These include Parkinson's disease, ADHD, schizophrenia, and mood disorders, which show stark differences in prevalence and outcome between men and women. In order to reveal the influence of biological sex as a risk factor in these disorders, there is a critical need to collect fundamental information about basic propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…The order of rodent strain effects (from decreased to increased discounting) indicated that Wistar > Lister Hooded > Sprague Dawley > Long Evans. It has been reported that dopaminergic differences exist between strains (Jiao et al 2003;Zamudio et al 2005;Novick et al 2008;McDermott and Kelly 2008;Rivera-Garcia et al 2020). Consistent with the meta-analytic effect, Wistar rats have been shown to exhibit higher levels of DAT than Sprague Dawley rats (Zamudio et al 2005).…”
Section: Rodent Strainsupporting
confidence: 59%
“…The order of rodent strain effects (from decreased to increased discounting) indicated that Wistar > Lister Hooded > Sprague Dawley > Long Evans. It has been reported that dopaminergic differences exist between strains (Jiao et al 2003;Zamudio et al 2005;Novick et al 2008;McDermott and Kelly 2008;Rivera-Garcia et al 2020). Consistent with the meta-analytic effect, Wistar rats have been shown to exhibit higher levels of DAT than Sprague Dawley rats (Zamudio et al 2005).…”
Section: Rodent Strainsupporting
confidence: 59%
“…However, peripubertal sex hormones do not seem to play a role in establishing these sex-specific DA receptor patterns (Andersen et al, 2002 ). Sex differences in striatal DAergic structure and function have recently been suggested to be strain-dependent, with some of the sex-specific characteristics commonly seen in Sprague-Dawley rats not observable in Long-Evans rats (Rivera-Garcia et al, 2020 ), highlighting the need for the consideration not only of sex but also species and strain in experimental design. More evidence is needed to determine whether the sex differences observed in adult DA circuitry result from puberty-dependent or puberty-independent developmental processes.…”
Section: Mechanisms Underlying Mesocorticolimbic Dopamine Circuit Organization In Adolescencementioning
confidence: 99%
“…For example, clinical imaging studies have revealed brain region- and sex-specific variations in dopamine transporter (DAT) availability in depression [ 35 ], and dopamine D2-like receptor densities with nicotine addiction [ 36 , 37 ]. Animal studies have also been particularly useful at providing some understanding as to how the dopamine system may differ innately between males and females, with reports evaluating sex differences in dopamine release [ 38 , 39 ], and dopamine receptor expression, in both adult animals and during development [ 15 , 40 , 41 , 42 , 43 ]. As well, differences in functional and behavioural responses to dopamine receptor agonists and antagonists have been observed, which include sex-specific differences in decision making and learning [ 44 , 45 ], anxiety and depression-like behaviour [ 43 , 46 ], and reward [ 39 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%